Peran Pemasukan Daerah terhadap Belanja Modal dalam Perspektif Maqashid Syariah - Faisal Hidayat; Rika Widianita; Miftahurrahmah Miftahurrahmah (STES Islamic Village, 2023)
Maqashid Shariah, a comprehensive framework of Islamic jurisprudence, ensures the preservation and advancement of human welfare by upholding five fundamental pillars that encompass the basic needs of individuals: Preservation of Religion (Hifzu ad-Din), Preservation of Life (Hifzu an-Nafs), Preservation of Intellect (Hifz al- Aql), Preservation of Progeny (Hifzu an-Nasb), and Preservation of Wealth (Hifzu al-Maal). This research aims to analyze the influence of regional revenues on capital expenditure from the perspective of Maqashid Shariah. The study employs a quantitative descriptive approach, utilizing the Fixed Effect Model (FEM) as the statistical analysis method with Eviews 10 software. The findings derived from the FEM are subsequently subjected to analysis through the lens of Maqashid Shariah theory. The results demonstrate that Regional Original Revenue (PAD), General Allocation Fund (DAU), and Budgetary Surplus (SILPA) significantly and positively impact Capital Expenditure, while Population Size (JP) does not exhibit a significant influence. The analysis of Maqashid Shariah further reveals that capital expenditure should prioritize essential needs in accordance with the principles of Maqashid Shariah, rather than being solely determined by population size. This research contributes to the understanding of the relationship between regional revenues and capital expenditure within the framework of Maqashid Shariah, emphasizing the importance of aligning economic decisions with the objectives of Shariah in promoting the well-being of society.